ANALISIS PEMOTONGAN RAMP POROS BUBUNGAN TERHADAP KONSUMSI BAHAN BAKAR DAN EMISI GAS BUANG PADA SUZUKI SHOGUN 125 SP TAHUN 2005 - Mulyono, Mulyono (Jurnal Nosel, 2013)
Based on results an analysis of cutting camshaft ramp to fuel consumption and exhaust gas emissions the suzuki shogun 125 sp in 2005, can be results of this study show that the fuel consumption average on the use of standard cam shaft for a distance of 100 km is 2777 ml. While fuel consumption average on the use of modified camshafts (duration 255o) for a distance of 100 km is 2887 ml. On the use of modified camshafts, fuel consumption for a distance of 100 km increased 110 ml. On the use of the standard exhaust camshafts CO emissions average is 1,396%. CO exhaust emissions on average use modified camshafts (duration 255o) is 5,583%. On the use of modified camshafts, CO emissions increased by 4,187%. HC exhaust emissions in the use of the average standard ridge axis is 141,667 ppm. HC exhaust emissions on average use modified camshafts (duration 255o) was 2621,33 ppm. On the use of modified camshafts HC emissions increased by 2479,663 ppm. The conclusions of this research is cutting ramp duration camshafts for 255o tend to increase fuel consumption, exhaust emissions CO and HC exhaust emissions on a motorcycle Suzuki Shogun 125 SP in 2005.